A Novel Phytochemical, DIM, Inhibits Proliferation, Migration, Invasion and TNF-α Induced Inflammatory Cytokine Production of Synovial Fibroblasts From Rheumatoid Arthritis Patients by Targeting MAPK and AKT/mTOR Signal Pathway - Du, Hongyan; Zhang, Xi; Zeng, Yongchang; Huang, Xiaoming; Chen, Hao; Wang, Suihai; Wu, Jing; Li, Qiang; Zhu, Wei; Li, Hongwei; Liu, Tiancai; Yu, Qinghong; et al. (Frontiers in Immunology, 2019)
In rheumatoid arthritis(RA) pathogenesis, activated RA fibroblast-1ike synoviocytes (RA-FLSs) exhibit similar proliferative features as tumor cells and subsequent erosion to cartilage will eventually lead to joint destruction. Therefore, it is imperative to search for compounds, which can effectively inhibit the abnormal activation of RA-FLSs, and retard RA progression.3′3-Diindolylmethane (DIM), the major product of the acid-catalyzed oligomerization of indole-3-carbinol from cruciferous vegetables, has been reported to be functionally relevant to inhibition of migration, invasion and carcinogenesis in some solid tumors. In this study, we explored the anti-proliferation, anti-metastasis and anti-inflammation effects of DIM on RA-FLSs as well as the underlying molecular mechanisms. To do this, primary RA-FLSs were isolated from RA patients and an animal model. Cell proliferation, migration and invasion were measured using CCK-8, scratch, and Transwell assays, respectively. The effects of DIM on Matrix metalloproteinases (MMPs) and some inflammatory factors mRNA and key molecules such as some inflammatory factors and those involved in aberrantly-activated signaling pathway in response to tumor necrosis factor α(TNF-α), a typical characteristic mediator in RA-FLS, were quantitatively measured by real-time PCR and western blotting. Moreover, the effect of DIM on adjuvant induced arthritis(AIA) models was evaluated with C57BL/6 mice in vivo. The results showed that DIM inhibited proliferation, migration and invasion of RA-FLS in vitro. Meanwhile, DIM dramatically suppressed TNF‐α –induced increases in the mRNA levels of MMP-2, MMP-3, MMP-8 and MMP-9; as well as the proinflammatory factors IL-6, IL-8 and IL-1β. Mechanistic studies revealed that DIM is able to suppress phosphorylated activation not only of p38, JNK in MAPK pathway but of AKT, mTOR and downstream molecules in the AKT/mTOR pathway. Moreover, DIM treatment decreased expression levels of proinflammatory cytokines in the serum and alleviated arthritis severity in the knee joints of AIA mice. Taken together, our findings demonstrate that DIM could inhibit proliferation, migration and invasion of RA-FLSs and reduce proinflammatory factors induced by TNF-α in vitro by blocking MAPK and AKT/mTOR pathway and prevent inflammation and knee joint destruction in vivo, which suggests that DIM might have therapeutic potential for RA.